Tecer o visível e entretecer o invisível: As cidades invisíveis, de Italo Calvino, e Como me contaram: fábulas historiais, de Maria José de Queiroz - Maria Silvia Duarte Guimaraes (2019)
In 1972, Italo Calvino published The invisible cities, a novel that refers to Il milione, written by Marco Polo in the thirteenth century. Through historical sites and characters, Calvino develops the concept of invisible city, which shall be of great importance to the analysis presented on this thesis. In 1972, Maria José de Queiroz published Como me contaram: fábulas historiais, a collection of poems, short stories and an epitaph, in which the historical and cultural past of Minas Gerais is rewritten. The aim of this thesis is to develop a comparative study of both books, as well as to reflect on the concept of invisible city, as proposed by Calvino, and how it can enlighten a reading of Como me contaram: fábulas historiais. In this way, shall be analyzed the relations between reality and fiction, the written and the unwritten world, cities and literature. I will base my arguments in Walter Benjamin, Ángel Rama and Renato Cordeiro Gomess works.